2015
DOI: 10.1371/journal.pone.0139024
|View full text |Cite
|
Sign up to set email alerts
|

A Patient-Centered Understanding of the Referral System in Ethiopian Primary Health Care Units

Abstract: BackgroundPrimary healthcare systems in sub-Saharan Africa have undergone substantial development in an effort to expand access to appropriate facilities through a well-functioning referral system. The objective of this study was to evaluate the current patterns of seeking prior care before arriving at a health center or a hospital as a key aspect of the referral system of the primary health care unit (PHCU) in three regions in Ethiopia. We examined what percentage of patients had either sought prior care or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 9 publications
1
37
2
Order By: Relevance
“…In this study, among the referred cases majority 108(87.8%) of women were referred from health center to primary hospital. This nding is higher than study conducted in Ethiopia which indicated that among the referred cases to the hospital, most (74%) had been referred by health center (14), and also different from study conducted in Nigeria in which most of the patients referred were from private clinics (15). The difference in the Ethiopian studies may be attributed to difference in study period and for the Nigeria study it might be because of the structures of health care delivery systems.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In this study, among the referred cases majority 108(87.8%) of women were referred from health center to primary hospital. This nding is higher than study conducted in Ethiopia which indicated that among the referred cases to the hospital, most (74%) had been referred by health center (14), and also different from study conducted in Nigeria in which most of the patients referred were from private clinics (15). The difference in the Ethiopian studies may be attributed to difference in study period and for the Nigeria study it might be because of the structures of health care delivery systems.…”
Section: Discussioncontrasting
confidence: 72%
“…In another study only 10% of patients were referred and majority of (74%) patients in the hospital were referred by a health center whereas among those who were referred to the health center, 32% came from a nearby hospital and only 18% referred from health post (14). A study in Nigeria revealed that only (7.1%) of patients were referred to the hospital mostly from private clinics while the rest (92.9%) were selfreferral (15).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of primary health care elements providing essential care and prevention resources for rural populations in Ethiopia, patients often access secondary levels of care without first using primary health care provided by primary level health facilities [7]. The study conducted in western Ethiopia at general hospital revealed 82% of patients bypassed the first level referral facilities and 74.9% of them did not first contact nearest health facilities [8] and the fundamental message of referral system is still unchanged [9].…”
Section: Introductionmentioning
confidence: 99%
“…Our study only included referrals if the referring facility made a referral phone call or if a referral note was written. Finally, many patients will not utilise formal referral systems and will bypass lower levels of care 4 , we are unable to quantify this and therefore self-referrals are not included in our study.…”
Section: Limitationsmentioning
confidence: 99%
“…2 Referrals systems are essential to; ensure patients receive timely appropriate care; increase access to specialist services; increase uptake of primary healthcare and optimise hospital utilisation 3 . Presently, referrals systems in Low and Middle Income Countries (LMICs) and the interface between different levels of the health system are both under-utilised 4 and under-researched. 5 6 7 Whilst access to care is regularly described as a key issue in LMIC health systems, formal referral systems are rare, standardised data on how patients are referred through the health system is sparse and there is little evidence on interventions to improve referral 8 .…”
Section: Introductionmentioning
confidence: 99%